Latina/o school principals: identity, leadership and advocacy. Issue 3 (26th May 2016) - Murakami, Elizabeth T.; Hernandez, Frank; Mendez-Morse, Sylvia; Byrne-Jimenez, Monica
Abstract : This study sought to further define and inform about the influence of Latina/o principals in schools as an alternative to traditional forms of leadership. The principals' Latina/o identity, their leadership styles and advocacy towards the improvement of student achievement were examined. This research focused on three questions: (a) How did Latina/o principals describe their schooling experiences?, (b) To what extent their racial/ethnic background created barriers or helped Latina/o leaders in their work as school administrators? and (c) What were the biggest challenges and successes in their current work as Latina/o school leaders? The findings indicate that Latinas/os connected their schooling experiences to those of their school's students. These experiences shaped their identity, leadership and advocacy towards students.